THE INFLUENCE OF STEM CUTTING TYPE AND IBA CONCENTRATION ON VEGETATIVE GROWTH OF BOUGAINVILLEA - Heti Herastuti; Siwi Hardiastuti EK (Techno LPPM, 2020)
Bougainvillea is one of the ornamental plants usually use for landscaping because of its colorful leaves and flowers. It is also used as a stabilizer and environmental preserver of pollution. This plant is propagated by cutting, however, there is a need to ensure easy growth of roots. Therefore, the purpose of this research was to determine the influence of stem cutting type and IBA concentration on vegetative growth of bougainvillea. The study was conducted in the experimental garden of the Faculty of Agriculture, UPN "Veteran” Yogyakarta, between October 2019 and January 2020 using a Randomized Completely Block Design (RCBD) with a factorial arrangement. The factors include the terminal, middle, and basal types of stem cutting while the IBA concentration was varied between 50, 100, 150 ppm and without IBA. The result showed 100 ppm IBA on the middle and basal type produced higher shoot number and shoot length of bougainvillea. The middle and basal type produced the best of percentage cutting to life, root number, length of longest root, and root volume. The giving IBA in cuttings produced the better root growth than without IBA.